Effect of Science Training on Competency with Soft Skills and Certification as Moderation variables - Warna, Hindalah; Rosidi, Rosidi; Farhan, Djuni (MEC-J (Management and Economics Journal), 2020)
Human resource training activities at UPT BLK Singosari are non-formal education programs organized by the government to provide soft skills and certification for trainees. The training, and soft skills and certifications should increase the traineeâ€™s competency. Therefore, this study will examine the effect of training on competence moderated by soft skills and certification.Â  This is a survey research using explanatory research. This research was conducted at UPT BLK Singosari. This study used a sample of 60 respondents. However, there were 10 questionnaires whose filling was incomplete so that the processed samples were 50 questionnaires. Data was collected using a questionnaire and filled in by respondents. From the data obtained, a moderation analysis is done to examine the effect each variable. This research has three findings. First, training has positive and significant effect on competence. Second, soft skills strengthen the effect of training on competence. Third, certification strengthens the effect of training on competence.